A review on Neural Network and Ant Colony Optimization for Vehicle Traffic Analysis and Routing (International Journal of Engineering and Computer Science, 2017)
This paper contains study regarding artificial neural network and ant colony optimization. An artificial neural network is used for traffic analysis and ant colony optimization is used for finding shortest path. All the previous work regarding the topic did not used the combination of these two techniques. Traffic analysis is very important topic because traffic is increasing on the roads day by day.